Penggunaan Model Cooperative Integrated and Composition (CIRC) dalam Pembelajaran Meganalisis Unsur Pembangun Cerpen pada Siswa Kelas XI SMA Negeri 2 Subang - Maulana, Irpan (Universitas Mathla'ul Anwar Banten, 2020)
The ability of students in reading comprehension is relatively low, especially in analyzing the elements of short story builders, so a breakthrough in learning is needed that can improve students' ability to read comprehension through the use of CIRC learning models. The formulation of the problem in this study are (1) How is the ability to analyze the short story builder elements in class XI students of SMA Negeri 2 Subang? (2) How is the ability to analyze the short story building elements in class XI students of SMA Negeri 2 Subang by using the CIRC learning model? (3) Is the use of the CIRC method effectively used in learning to analyze the short story building elements? The objectives of this study are (1) Describe the ability to analyze short story builder elements in class XI students of SMA Negeri 2 Subang (2) Describe the ability to analyze short story builder elements in class XI students at SMA Negeri 2 Subang using the CIRC learning model. (3) Describe the effectiveness of using the CIRC method in analyzing the elements of the short story builder. This research uses the Pre-Experiment one group pretest-posttest desaign research method. In the initial data the results of this study averaged 63.06 while the average value obtained by students in the final test was 77.94. From both of these results indicate that there is an increase in the average value on the final test compared to the initial test before using the CIRC Learning model, so that the use of the CIRC learning model in analyzing the elements of short story builders can be said to be effective.